Effect of addition of melatonin on liquid storage of ram semen at 4°C. (29th January 2019) - Dai, Gui‐Chao; Meng, Yu; Zhang, Li‐kun; Du, Ye‐qing; Wen, Fei; Feng, Tian‐yu; Hu, Jian‐hong
Abstract: Adding a certain amount of antioxidants to semen extender has been shown to improve semen quality. The aim of present study was to elucidate whether the supplementation of melatonin to the Tris‐based extender (CTR) could enhance the quality of ram spermatozoa during storage at 4°C. Ram semen samples were collected and diluted with CTR extender containing different concentrations (0, 0.05 (M 0.05), 0.1 (M 0.1), 0.2 (M 0.2) or 0.4 (M 0.4) mM) of melatonin. Sperm routine indicators, mitochondrial activity, total antioxidant capacity (T‐AOC) and malondialdehyde (MDA) content were analysed in control and melatonin treatment groups. The higher per cent of motility, plasma membrane integrity, mitochondrial activity and T‐AOC activity was observed in M 0.05, M 0.1 and M 0.2 groups compared to control group at 5 days of storage ( p < 0.05), while lower percentage of MDA content was observed among these groups ( p < 0.05). In addition, there were no significant differences in acrosome integrity among the control and M 0.05, M 0.1 and M 0.2 groups during the experiment. The above results show that the addition of 0.05, 0.1, 0.2 mM of melatonin is beneficial to the preservation of ram semen during liquid storage at 4°C mainly through antioxidative stress.